PREDATION PRESSURE ON ARTIFICIAL CATERPILLARS INDICATES ENEMY-REDUCED TIME AND SPACE - Seifert, Carlo Lutz (Jihočeská univerzita, 2019)
This thesis explores patterns of predation on artificial caterpillars in two neotropical lowland rainforest ecosystems. The specific aim was to test if enemy-reduced time and space does exist for physical undefended caterpillars. Our results indicated that larval Lepidoptera are capable to lower predation risk by nocturnal foraging and by avoiding habitats of high light irradiance. Thus, habitat-specific host plant choice by adult females and a timely scheduled foraging behaviour of the caterpillars could remarkably increase the survival rate of immature stages.
PREDATION PRESSURE ON ARTIFICIAL CATERPILLARS INDICATES ENEMY-REDUCED TIME AND SPACE
Keywords: ants; caterpillars; foraging behaviour; Lepidoptera; predators; rainforest; ants; caterpillars; foraging behaviour; Lepidoptera; predators; rainforest